Your Vote is (no) Secret! How Low Voter Density Harms Voter Anonymity and Biases Elections in Italy - Mauro Caselli; Paolo Falco (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2019)
Italian voters are assigned to a specific polling station according to their address. After an election, candidates know how many votes they received in each polling station. When the number of voters per polling stations is low and candidates are many, this jeopardises the secrecy of voting and candidates can more easily detect deviations from pre-electoral pledges. Exploiting variation in the number of voters per polling station across cities and over time, combined with rich data on politicians in office in all Italian municipalities between 1989 and 2015, we estimate the effect of voter density on the probability of re-election for local politicians. We find that when the number of voters per polling station is lower (and secrecy is at greater risk), incumbents have a higher probability of re-election. The analysis addresses the potential endogeneity of voter density. The results are stronger in regions with lower social capital and worse institutions.
Keywords: 330